Alkaline hydrolysis to increase the selectivity of colorimetric determination of polysorbate. (September 2017) - Engelmaier, Andrea; Anderle, Heinz; Weber, Alfred
Abstract: Here, we describe a straightforward sample pretreatment step for the colorimetric cobaltthiocyanate determination of polysorbate, which circumvents the assay's shortcomings due to interference of protein and does not require complex instrumentation. Protein-containing test samples are hydrolyzed with strong alkali at 100 °C, neutralized and clarified by filtration before applying the colorimetric assay. The modified method performs with appropriate accuracy and precision, allowing specific polysorbate measurement in the presence of Triton X-100 during virus inactivation, determination of residual amounts of polysorbate in the final products and measurement of polysorbate 80 in final formulated products. The alkaline hydrolysis step, primarily designed to provide the assay's reliability in the presence of protein, also enhances its selectivity towards interference by the non-ionic detergent Triton X-100 and increases its robustness against changes in the fatty acid moiety of polysorbate as it released the fatty acid essentially contributing to the known heterogeneity of polysorbates. These results demonstrate that with sample pretreatment the handy colorimetric assay, not requiring complex instrumentation, can be used to measure polysorbate 80 concentrations in intermediates and final products of therapeutic protein solutions.